ТЕНДЕНЦІЙНІ НАПРЯМКИ РОЗВИТКУ ХОРОВОЇ ЛІТУРГІЙНОЇ ПРАКТИКИ В ГАЛИЧИНІ КІНЦЯ ХІХ ‒ ПЕРШОЇ ПОЛОВИНИ ХХ СТОЛІТЬ (World Science, 2018)
The article highlights trends in the development of choral liturgical practice in Galicia at the end of the nineteenth and the first half of the 20th century, which were formed on the basis of governmental innovations in the system of education and cathedral and church changes in Western Ukrainian lands. In this, the active role of numerous spiritual and secular choral ensembles had played an important role. At the same time, certain influence were played by touring groups, which, with the spiritual programs of works of the Dnieper-Dnieper composers, considerably deepened the evaluation criteria as the work of the Galician authors as well as the performing level of creative groups. All this testified to the need of Ukrainians in the spiritual cultural and artistic life, about comprehension of the essence of the ritual and chorister repertoire and the development of the national style of choral music. Confirmation of these processes was the spiritual choral heritage of the Galician composers of the late nineteenth and the first half of the twentieth century, represented in a wide genre variety. Thus, the article outlines the traditional and original author's approaches to the creation of liturgical music within the bounds of the statutory ritual system, the concept of «samolivka» and «jerusalimka» is illustrative for this period.